'The New Global Politics of Religion': religious harmony, public order, and securitisation in the post-colony. Issue 1 (2nd January 2018) - Hussin, Iza
Abstract: This article explores key concepts in legal reasoning on the issue of 'religious harmony' in Malaysia. It argues that the concept of religious harmony belongs to the realm of public order, and public order is indexed to the legal logic of internal security. In Malaysian legal reasoning, the genealogy of these concepts runs through India and the United Kingdom. Arguments for religious freedom based upon normative commitments to liberal rights do not take into account the institutional and legal logic of internal security, within which toleration has different stakes and meanings. When resources are deployed to support the state governance of religion in service of international security concerns, they further consolidate the confluence of internal security and religious harmony, often at the expense of religious minorities. Through a tracing of the reasoning and references of judges and litigants in a series of judgements on the uses of the word 'Allah' by Christians in Malaysia, this article details a post-colonial genealogy of religious harmony through concerns not for toleration or liberty, but for order.